Service Quality, Taxpayer Awareness and Effectiveness of the Samsat Drive Thru System on Motor Vehicle Taxpayer Compliance in Sidoarjo Regency during the Covid-19 Pandemic: Kualitas Pelayanan, Kesadaran Wajib Pajak dan Efektivitas Sistem Samsat Drive Thru Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Sidoarjo Pada Masa Pandemi Covid-19 - Savila Rahmahwati; Santi Rahma Dewi (Academia Open, 2021)
This study aims to determine Service Quality, Taxpayer Awareness, and Effectiveness of the Samsat Drive Thru System on Motor Vehicle Taxpayer Compliance in Sidoarjo Regency during the Covid-19 Pandemic. This study uses primary data, namely questionnaires distributed to 154 respondents using purposive sampling. The population used was students of the Accounting Study Program at Muhammadiyah Sidoarjo University in the 2017 and 2018 batches. The data analysis techniques used were descriptive statistical analysis, validity test, reliability test, multiple linear regression analysis, coefficient of determination test and t test using SPSS v.25 in data processing. The results of this study indicate that during the Covid-19 pandemic in Sidoarjo Regency, service quality had a significant effect on motor vehicle taxpayer compliance, taxpayer awareness had a significant effect on motor vehicle taxpayer compliance, and the effectiveness of the Samsat Drive Thru system had no effect on vehicle taxpayer compliance. motorized. This study aims to determine Service Quality, Taxpayer Awareness, and Effectiveness of the Samsat Drive Thru System on Motor Vehicle Taxpayer Compliance in Sidoarjo Regency during the Covid-19 Pandemic.